The Effectiveness of The Treasure Hunt Type Discovery Learning Model on Student Engagement in Islamic Education and Character Building - Putri Putri; Ruswanto Ruswanto; Ais Isti'ana (STAI Serdang Lubuk Pakam, 2025)
This study aims to increase student learning activity in Islamic Religious Education through the application of the Treasure Hunt type of Discovery Learning model. The background of this study stems from low student participation, especially in group discussions, due to monotonous conventional methods and limited access to technology. The method used is quantitative with an experimental design, involving 10th grade students at Tanjung Bintang 1 Public High School. The sample was selected using simple random sampling, with the control group using conventional methods and the experimental group receiving the Treasure Hunt type of Discovery Learning treatment. The instrument used was a learning activity questionnaire that was tested for validity and reliability. The results showed that the application of this model significantly increased student activity, especially in group discussions. The novelty of this research lies in the integration of Discovery Learning and the Treasure Hunt game in upper secondary Islamic Religious Education. This study shows that the combination of these two approaches creates an interactive and collaborative learning atmosphere and changes the role of the teacher to that of a facilitator.